Strengthening of business administration and medium-sized enterprises in export of gems and jewelry industry in Bangkok and vicinity - Klankaew, Amornwan; Krimjai, Natcha (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
Dissertation on "the strengthening of business administration, small and medium enterprises in the export of gems and jewelry in Bangkok and its vicinity," a weapon objectives were to (1) analyze the relationship between different factors. The impact of the strengthening of export enterprise jewelry and small and medium-sized enterprises in the Bangkok Metropolitan Area (2) to determine the consistency of models created with empirical data (3) to study factors. influence, both directly and indirectly to the strengthening of export enterprises Jewelry Thailand and medium-sized enterprises in the BMA. This research is a quantitative research. By analyzing the path of entrepreneurs, small and medium enterprises in the export of gems and jewelry in Bangkok and the vicinity of 399 people used a survey to determine the validity of a panel of experts. To calculate IOC and reliability testing with a correlation with the Akron Bush. The results showed that (1) Administration of manufacturing a positive influence on the strength of the Small Business Administration, small and medium enterprises hypothesis testing found. The research is based on an assumption that is latent in the production. There is a direct correlation positively to the strengthening of the Small Business Administration, small and medium enterprises significantly at 0.05. (2) The business of marketing a positive influence on the strength of the Small Business Administration, small and medium enterprises. The hypothesis testing found The research is based on an assumption that is latent in the market. There is a direct correlation positively to the strengthening of the Small Business Administration, small and medium enterprises significantly at 0.05. (3) Management Innovation has a strong positive influence on the management of small and medium-sized enterprises test that hypothesis. The research is based on the assumption that the latent innovation. There is a direct correlation positively to the strengthening of the Small Business Administration, small and medium enterprises significantly at 0.05. (4) Management has no positive influence on the financial strength of the business and medium-sized enterprises hypothesis testing found. The research is based on the assumption that the financial variables. There is no positive correlation between the strength of the Small Business Administration, small and medium enterprises were not significant at 0.05. Article history : Accepted 28 June 2016 SIMILARITY INDEX = 0.00